Effect of Sulfated Polysaccharide from Undaria pinnatifida (SPUP) on Proliferation, Migration, and Apoptosis of Human Prostatic Cancer - Xiaolin Xu; Xin Zhu; Wenglong Lu; Yandong He; Yihan Wang; Feng Liu (International Journal of Polymer Science)
Objective. To observe the effect of sulfated polysaccharide from Undaria pinnatifida (SPUP) on proliferation, migration, and apoptosis of human prostatic cancer. Methods. DU145 human prostate cancer cells were cultured in vitro, and the proliferation activity both in the control group and the SPUP treatment groups (25, 50, 100, 200 μg/ml) was measured by CCK-8 assay. The wound healing assay was conducted to detect the cell migration. Cell apoptosis was measured by flow cytometry. The protein and mRNA expressions of matrix metalloproteinase-9 (MMP-9) and apoptosis-related factor Bax were detected by qRT-PCR and Western blot. The expressions of cleaved caspase-3 and cleaved caspase-9 were also determined by Western blot. Results. (1) CCK-8 results showed that the proliferative activity of DU145 cells was significantly decreased with the increase of SPUP treatment concentration (P<0.05) in a dose-dependent manner and that the inhibitory effect of SPUP was most significant at 72 h (P<0.05) as compared with the control group; (2) the migration rate of SPUP-treated cells was significantly decreased (P<0.05) as compared with the control group. And the results of qRT-PCR and Western blot assays showed that SPUP inhibited the expression of MMP-9 in DU145 cells; (3) compared with the control group, the SPUP-treated groups had increased apoptosis of the cells. The expressions of apoptosis-related factors cleaved caspase-3, cleaved caspase-9, and Bax were upregulated (P<0.05), and the mRNA expression of Bax was increased (P<0.05). Conclusion. SPUP showed an antitumor activity in prostatic cancer, and the underlying mechanism may be pertaining to inhibition of migration, proliferation, and induction of apoptosis of cancer cells.